PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES BERMUATAN CHEMO-ENTREPRENEURSHIP PADA MATERI GUGUS FUNGSI SENYAWA KARBON - Riawati Rahayu; Retno Aliyatul Fikroh; Dewi Ratna Sari; Pandu Ridzaniyanto (Lantanida Journal, 2022)
Google sites can be used as interactive chemistry learning media, especially on the functional group material of carbon compounds. This study aims to develop learning media based on google sites containing chemo-entrepreneurship (CEP) on the functional group material of carbon compounds and determine product quality based on the assessment of material experts, media experts, reviewers (high school chemistry teachers), and student responses. Research and Development (R&D) is a research method with a 4-D development model consisting of define, design, develop, and disseminate but limited to the develop stage. Product quality was assessed by a material expert, a media expert, five reviewers, and ten students responded. Quality assessment was carried out using the expert judgment using a Likert scale while the response data used the Guttman scale. The product developed is a website developed through the Google Sites containing a home page, materials, evaluations, unique facts, and references. The results of the assessment according to material experts, media experts and reviewers were 89.28%, 87.5% and 94.41%, respectively, and received a positive response from students of 97.5%. Based on these results, it can be concluded that google sites can be used as an alternative chemistry learning media.